Editorial: The Family in Antiquity and the Modern Times - Anna Królikowska (Jesuit University Ignatianum in Krakow, 2020)
The reflection undertaken in this issue is the family as the oldest and fundamental social group present at all stages of the development of society. Many researchers of family issues emphasise that the family is an inherent and irreplaceable element of the social structure, because it is a natural and indispensable environment of human birth and development; an environment in which different generations - both children and adults - coexist and interact with one another. These mutual interactions carry with themselves both social and upbringing significance.